2022
DOI: 10.1136/bmjopen-2021-059878
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and behavioural exposure pathways associated with diarrhoea and enteric pathogen detection in 5-month-old, periurban Kenyan infants: a cross-sectional study

Abstract: ObjectivesThe aim of this study was to test whether household environmental hygiene and behavioural conditions moderated associations between diarrhoea and enteric pathogen detection in infants 5 months of age in Kenya and pathogen sources, including latrine access, domestic animal co-habitation and public food sources.DesignCross-sectional study utilising enrolment survey data of households participating in the Safe Start cluster-randomised controlled trial .SettingKisumu, Kenya.ParticipantsA total of 898 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…For this reason, men have less access to WASH services than women, increasing their susceptibilities to pathogens like bacteria, viruses and parasites. 32 , 33 This finding supports Kayser et al 35 who found that there are disparities in access to WASH between males and females. These disparities are problematic because Conflict Theory holds that conflicts and wars affect human health as well as access to WASH levels.…”
Section: Discussionsupporting
confidence: 71%
“…For this reason, men have less access to WASH services than women, increasing their susceptibilities to pathogens like bacteria, viruses and parasites. 32 , 33 This finding supports Kayser et al 35 who found that there are disparities in access to WASH between males and females. These disparities are problematic because Conflict Theory holds that conflicts and wars affect human health as well as access to WASH levels.…”
Section: Discussionsupporting
confidence: 71%
“…DNA and RNA from infant and animal faeces is analysed as previously described using microfluidic TaqMan Array cards containing primers and probes for Norovirus GI and GII, adenovirus 40/41, Sapovirus , Enterovirus , Rotavirus, Salmonella enterica , Shigella/EIEC backbone, Shigella/EIEC plasmid, Campylobacter jejuni/coli, Listeria monocytogenes, Clostridium difficile , Helicobacter pylori , enterotoxigenic Escherichia coli LT/ST, enteropathogenic E. coli , enteroaggregative E. coli and Shiga-like toxin-producing E. coli stx1/stx2, Enterocytozoon bieneasi , Giardia , Cryptosporidium spp., Entamoeba histolytica and the MS2 extrinsic control. Most of these pathogens were selected based on prior evidence that they are commonly transmitted in Kenya, with a few like H. pylori and L. monocytogenes being selected based on potential of transmission 68–70. The TaqMan assays are run on a QuantiStudio 12K Flex Real-Time PCR System (ThermoFisher, Chicago, Illinois).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The international literature has extensively assessed the relationship between diarrhea and WASH services [ 2 , 7 , 8 ]. Additionally, previous studies have focused on factors other than WASH that might govern contamination pathways, notably poor housing conditions and cohabitation with animals [ 9 ], food handling [ 10 ], and exposure to environmental sources of pathogens in public spaces [ 11 ]. These studies reflect a renewed interest in environmental health determinants and raise the need for a broader approach to address variations in morbidity and mortality patterns across populations based on socioeconomic and housing conditions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is inscribed within this broader approach by looking at specific housing deprivation characteristics as environmental exposures of interest and confronting the latter’s spatial distribution to that of diarrheal cases (health outcomes of interest). Although previous studies have already assessed relations between housing deprivation and diarrheal diseases in SSA [ 9 , 13 ], besides a few exceptions [ 14 , 15 ], there is a paucity of empirical evidence elaborated on a cartographic basis and at a high spatial resolution (i.e., with precise maps of the built environment, housing characteristics, and cases of diarrhea). This “spatially explicit” approach is critical for urban planners to assess disease risk factors related to the built environment and plan tailored interventions.…”
Section: Introductionmentioning
confidence: 99%